2006
DOI: 10.1128/aem.72.1.956-959.2006
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Biofilm-Forming Subpopulations upon Exposure of Escherichia coli to Environmental Bacteriophages

Abstract: Exposure of Escherichia coli MG1655 to environmental bacteriophages results in rapid selection for phage-tolerant subpopulations displaying increased biofilm formation. Analysis of one phage-tolerant strain revealed large amounts of the DNA-binding Dps protein in the outer membrane protein and production of fimbria-like structures. In dps and fimA mutant derivatives of MG1655, no selection of phage-tolerant bacteria upon exposure to bacteriophages occurred, suggesting a role for Dps and type I pili in bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 25 publications
2
48
0
1
Order By: Relevance
“…Despite Dps being a cytoplasmic protein, we also detected its presence in the outer membrane fraction (band 11, Fig. 2C), as already reported for other biofilm-forming E. coli strains (34), thus suggesting that a fraction of the Dps protein might be associated with the outer membrane. Unlike Dps, CsgG and OmpW are bona fide outer membrane proteins (38,49).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Despite Dps being a cytoplasmic protein, we also detected its presence in the outer membrane fraction (band 11, Fig. 2C), as already reported for other biofilm-forming E. coli strains (34), thus suggesting that a fraction of the Dps protein might be associated with the outer membrane. Unlike Dps, CsgG and OmpW are bona fide outer membrane proteins (38,49).…”
Section: Resultssupporting
confidence: 57%
“…Such coordination would relay the transition from single cell to biofilm to expression of the rpoS regulon, i.e., one of the main stress responses in bacteria (29). Interestingly, biofilm formation in E. coli, even when independent of CsgD and of curli production, appears to be tightly connected to S -dependent gene expression (1,4,17,34,62) and to general induction of stress responses (4, 54), possibly FIG. 7. S turnover experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the positive effects of phages on the biofilm forming capacities in certain strains of E. coli. Combination of E. coli strain K-12 MG1655 (phage tolerant strain) with P1vir or λ phages has increase the biofilm forming capacities within 24hrs and the presence of Type I fimbria stimulated the mechanism [63].…”
Section: Irreversible Attachmentmentioning
confidence: 99%
“…Exposure of E. coli carrying conjugative plasmid biofilms to male-specific bacteriophages also has not been investigated yet. Of these, the previous studies mainly focused on lytic-bacteriophages, such as l, T4 or T7, which failed to penetrate through biofilms because of the presence of exopolymers (Doolittle et al, 1995(Doolittle et al, , 1996Corbin et al, 2001) and/or fimbriae (Lacqua et al, 2006). In addition, many lytic bacteriophages are unable to replicate efficiently in the F-plasmid carrying E. coli (Garcia and Molineux, 1995).…”
mentioning
confidence: 99%